THE EFFECT OF QUANTUM LEARNING BASED WITH MIND MAPPING TOWARDS SCIENCE ACHIEVEMENT OF FIFTH GRADE ELEMENTARY STUDENTS - PD Anggaraeni; I G A O Negara; I K A Putra (Journal of Psychology and Instruction, 2018)
The aim of this research is to know the significant influence of Quantum learning based with mind mapping towards the results of science achievement of fifth grade elementary students of Cluster I in Kuta Utara district in academic year of 2017/2018. It was quasi experimental research with nonequivalent control group design. The population of this research was 339 fifth grade students in Cluster I in Kuta Utara district. The sample was chosen by random sampling. It was obtained that fifth grade A students of SD No. 7 Dalung (34 students) as experimental group and the fifth grade A students of SD No. 4 Dalung (28 students) as control group. The data were collected by using objective test of multiple choice. Around 40 items have been validated. The collected data were analyzed using descriptive statistics and inferential statistics of t-test analysis. Based on the result of t-test analysis, there were obtained tvalue = 6,778 and ttable (at a significance level of 5% with dk = (34+28)-2 = 60) = 2,000. This indicated that tvalue > ttable so it could be concluded that there was significant difference of science achievement between the groups taught by Quantum Learning based with Mind Map and the groups taught by Conventional Learning. It can be concluded that there was the effect of Quantum learning model with mind mapping towards the science achievement of fifth-grade elementary students of Cluster I in Kuta Utara district in academic year of 2017/2018.